2016
DOI: 10.3389/fmicb.2016.01387
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Type III Secretion System 2 ATPase EivC Is Involved in the Motility and Virulence of Avian Pathogenic Escherichia coli

Abstract: Type III secretion systems (T3SSs) are crucial for bacterial infections because they deliver effector proteins into host cells. The Escherichia coli type III secretion system 2 (ETT2) is present in the majority of E. coli strains, and although it is degenerate, ETT2 regulates bacterial virulence. An ATPase is essential for T3SS secretion, but the function of the ETT2 ATPase has not been demonstrated. Here, we show that EivC is homologous to the β subunit of F0F1 ATPases and it possesses ATPase activity. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 65 publications
3
37
0
Order By: Relevance
“…F2_18C possesses the full complement of ETT2 genes (Figure 5A), however an IS1F insertion interrupts the eivG gene, and eivC gene is truncated. The latter observation may be particularly important as eivC is involved in motility, serum resistance and intramacrophage survival, at least in avian pathogenic E. coli (APEC) (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…F2_18C possesses the full complement of ETT2 genes (Figure 5A), however an IS1F insertion interrupts the eivG gene, and eivC gene is truncated. The latter observation may be particularly important as eivC is involved in motility, serum resistance and intramacrophage survival, at least in avian pathogenic E. coli (APEC) (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Also, Wang et al demonstrated that the components of the type 3 secretion system (T3SS) play roles in virulence and intracellular survival of an avian-pathogenic E. coli (APEC) strain in macrophages ( 49 ); thus, roles of such factors might also influence adhesion and invasion of ExPEC strains. In Gram-negative bacteria, the majority of serine proteases secreted by the autotransporter pathway are implicated in virulence ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutational analysis of the ETT2 cluster in an avian pathogenic E. coli showed it had reduced virulence, even though the cluster had undergone mutational attrition and could not encode a functional T3SS, suggesting potential alternative roles in pathogenesis 19 . Other studies have also suggested a role for proteins encoded in the ETT2 in virulence of avian pathogenic E. coli and K1 strains [20][21][22] . A recent study examined the role of the putative transcriptional regulator gene eilA at the selC locus in EAEC strain O42 18 .…”
mentioning
confidence: 95%